Understanding and use of food package nutrition label among educated young adults - Hazali, Norazlanshah (Asian Network for Scientific Information, 2012)

(untitled)
Nutrition information on food labels has become one of the major components included in Malaysian Dietary Guideline in order to promote healthy dietary habits among Malaysians. This study was aimed to assess the understanding on nutrition label information and ability to perform common nutrition label task and to explore the extent of nutrition label usage as well as the reason associated with the intensity of label used among educated young adults. Cross sectional study conducted by distributing 357 self administered questionnaires among students in UiTM Puncak Alam and only 295 returned (response rate = 82.6%). The questionnaires collected information of demographics, nutrition knowledge and understanding, nutrition label task, item used on nutrition label and the reason of nutrition label use. The mean ages are 21±1.745 which most of the respondent currently study at degree (73.9%) and diploma (26.1%) level. The nutrition knowledge means score 12.08±4.287 where about 37.6% have low knowledge and only 30.5% have good knowledge. In nutrition label task section, majority of the subjects (69.5%) unable to perform resulting in mean score 0.94±1.097. The most item used on food labels are ingredient list (78.3%) while percent daily value information are the least use (56.5%) by the subjects. More than half (53.6%) of the subjects do not use the nutrition label mainly because they do not understand the terms on the label (32.4%). In contrast, the label user uses the label to assess specific nutrient content of the food (38.4%). The level of nutrition knowledge is significantly associated with performance on nutrition label task (p=<0.001) where high proportion of subject with low nutrition knowledge unable to perform the nutrition label task. In conclusion, this study found that there is low understanding of nutrition knowledge and use of nutrition label among young adults. © Asian Network for Scientific Information, 2012.